(3ZQGFH GdbQBf hQZGFH GdaQbGfs - (3fXGe GdOjf MSf Hf eMeO Hf MSjf Gdbej GdfjSGHhQj fXGe GdGYQL,J (B728 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdCYQGa s
(3BNQgG (B:s
(3jfJgi HfgGjI GdJaSjQ s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfi ef GdfSNI faSgGs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs